PENYULUHAN PENGGUNAAN OBAT BEBAS DAN OBAT BEBAS TERBATAS SEBAGAI UPAYA PENINGKATAN LITERASI OBAT DI KALANGAN PELAJAR: HEALTH EDUCATION ON OVER-THE-COUNTER (OTC) AND LIMITED OTC DRUG USE AS AN EFFORT TO IMPROVE MEDICINE LITERACY AMONG STUDENTS - Rangkuti, Irma Yanti; Nofi Susanti; Syahadatina (Jurnal Kedokteran Ibnu Nafis, 2025)
Self-medication, or the use of medication without a prescription, is a common practice in society, including among students. A lack of understanding regarding drug classification, packaging labels, and proper usage can lead to various risks such as medication errors, side effects, and drug resistance. This community service activity aimed to improve medicine literacy by providing education about over-the-counter (OTC) and limited OTC drugs to female vocational school students. The program was conducted at Vocational School in Medan, involving 30 participants. The intervention included a lecture session, pre-test and post-test assessments, and interactive discussions. The analysis showed an increase in knowledge scores by 4.1 points with a p-value of 0.00. This activity proved effective in enhancing adolescents’ understanding of rational drug use.